Electrospun Jets Number and Nanofiber Morphology Effected by Voltage Value: Numerical Simulation and Experimental Verification - Zhi Liu; Kaiyi Ju; Zongqian Wang; Wei Li; Huizhen Ke; Jihuan He (Nanoscale Research Letters, 2019)
Abstract Electrical voltage has a crucial effect on the nanofiber morphology as well as the jet number in the electrospinning process, while few literatures were found to explain the deep mechanism. Herein, the electrical field distribution around the spinning electrode was studied by the numerical simulation firstly. The results show that the electrical field concentrates on the tip of a protruding droplet under relatively low voltage, while subsequently turns to the edge of needle tip when the protruding droplet disappears under high voltage. The experimental results are well consistent with the numerically simulated results, that is, only one jet forms at low voltage (below 20 kV for PVDF-HFP and PVA nanofiber), but more than one jet forms under high voltage (two jets for PVDF-HFP nanofiber, four jets for PVA nanofiber). These more jets lead to (1) higher fiber diameter resulting from actually weaker electrical field for each jet and (2) wide distribution of fiber diameters due to unstable spinning process (changeable jet number/site/height) under high voltage. The results will benefit the nanofiber preparation and application in traditional single-needle electrospinning and other electrospinning methods.